Differences in the frequency of macrophage and T cell markers between focal and crescentic classes of anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis - Dana Kidder; Susan E Bray; Stewart Fleming (Society of Diabetic Nephropathy Prevention, 2017)
Background: Anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (AAGN) can be classified into; focal, crescentic, mixed and sclerotic classes. Macrophages and T lymphocytes are key players in mediating renal injury. The frequency of macrophage and T lymphocytes in different histological classes is unclear. Objectives: We examined the frequency of macrophage and T lymphocyte markers in AAGN and assessed their correlation with renal function at presentation. Patients and Methods: Renal biopsies from 38 patients were included in immunohistochemistry analysis of macrophages (CD68, sialoadhesin [Sn] and mannose receptor [MR]) and T cells (CD4 and CD8) markers. The frequency of these markers in glomerular, periglomerular and interstitial compartments were measured in a blinded fashion. Biopsies were allocated a histological class of focal, crescentic, mixed or sclerotic. Scores were then matched to histological class and assessed for correlation with renal function. Results: The biopsies were crescentic 19 (50%), focal 10 (26.3%), mixed 6 (15.7%) and sclerotic 3 (8%). Interstitial CD68+ macrophages and CD8+ T lymphocytes showed best correlation with renal function at the time of presentation. CD68+ macrophages were significantly increased in crescentic compared to focal AAGN. MR+ macrophages, CD4 and CD8 T cells were also elevated in the interstitium of crescentic compared to focal group. Conclusions: In this study interstitial CD68 and CD8 showed the highest association with the renal function at presentation. Differences in the cellular infiltrate between focal and crescentic AAGN were related to CD68+ macrophages and to interstitial MR+ macrophages and T lymphocytes. Further studies are needed to assess these differences across all four histological categories.